Association between parental stress and adolescent behavior mediated by parenting style in public junior and senior high school students in North Jakarta - Valerie, Valerie; Wijaya, Ellen; Setiawan, Andy; Astiarani, Yunisa; Surya, Junita Elvira Pandji (Paediatrica Indonesiana, 2025)
Background Parental/ primary caregivers’ stress levels and parenting styles can impact parental behavior towards adolescent children, leading to potential shifts in the children's behavior. Parenting styles are classified into three types: authoritarian, authoritative, and permissive. Authoritarian parenting enforces strict rules with one-way communication, limiting children's creativity and independence. Authoritative parenting fosters two-way communication, balancing clear expectations with reasoning. Permissive parenting emphasizes open communication with minimal discipline, granting children greater decision-making freedom. Objective To explore the association between parental stress, parenting style, and adolescent behavioral problems. Methods This cross-sectional study was conducted on 981 adolescents and their primary caregivers. Parental stress, parenting style, and adolescents’ behavior were assessed through questionnaires. The distribution of respondents’ characteristics was obtained by univariate analysis. Bivariate analysis was performed using direct effect of path analysis to look for associations between the two categorical variables. Multivariate analysis used path analysis to determine all variables’ direct and indirect relationships. Results Of 981 adolescent respondents, 665 behaved normally (67.85%) and 552 (56.3%) received authoritative parenting.  Of 981 primary caregivers, 690 had moderate stress levels (70.3%). The study found a significant correlation between parental stress levels and various aspects of child behavior (P<0,05), including emotional symptoms, behavioral issues, hyperactivity, peer relationship difficulties, and prosocial behavior. Parental stress levels were negatively associated with authoritative parenting (P<0.05). Authoritarian parenting was associated with peer problems and behavioral problems (p<0.05) in adolescents. In the gender segmentation test, authoritarian parenting had a positive relationship with behavior problems in boys (P<0.05) and peer problems in girls (P<0.05). Conclusion Most adolescents had normal behavior and received authoritative parenting. Parental stress had a positive  association with adolescents’ behavior. Children who experienced authoritarian parenting tended to have peer and behavioral problems. Boys who experienced high authoritarian parenting are at higher risk of abnormal behavioral problems. Girls who experienced authoritarian parenting are at higher risk of peer problems. Parenting style was not a mediator between parental stress and adolescent behavior.